2021
DOI: 10.1002/chem.202100670
|View full text |Cite
|
Sign up to set email alerts
|

Carbo‐mer of Barrelene: A Rigid 3D‐Carbon‐Expanded Molecular Barrel

Abstract: After extensive studies of 1D and 2D skeletal carbo-mers based on C 8 π-conjugating dialkynylbutatriene units (DABs:~C � CÀ (R)C=C = C=C(R)À C � C~) bridging sp or sp 2 centers in carbo-butene, carbo-xylylene or carbobenzene derivatives, 3D versions are envisaged through carbo-barrelenes and partially reduced derivatives thereof where two or three DAB blades span a bridge between sp 3 carbinol vertices or ether thereof. For R = Ph, stable representatives were synthesized through a pivotal [6] pericyclynedione,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…Knowing the stronger magnetic aromatic character of C 18 rings with respect to C 6 phenyl rings from previous studies (as indicated by comparison of 1 H NMR spectra at low field), [6,22,25] the local aromaticity of carbo-stilbenes was assessed using the nucleus-independent chemical shift (NICS), a metric introduced by Schleyer and colleagues, serving as a general scalar descriptor of algebraic magnetic (anti)aromaticity. [26] NICS is defined as the negative absolute shielding value computed at a ring center (NICS(0)), or 1 Å above or below it (NICS(1) and NICS(À 1)).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Knowing the stronger magnetic aromatic character of C 18 rings with respect to C 6 phenyl rings from previous studies (as indicated by comparison of 1 H NMR spectra at low field), [6,22,25] the local aromaticity of carbo-stilbenes was assessed using the nucleus-independent chemical shift (NICS), a metric introduced by Schleyer and colleagues, serving as a general scalar descriptor of algebraic magnetic (anti)aromaticity. [26] NICS is defined as the negative absolute shielding value computed at a ring center (NICS(0)), or 1 Å above or below it (NICS(1) and NICS(À 1)).…”
Section: Resultsmentioning
confidence: 99%
“…[18,19] The cis -> trans isomerization is however frozen in endocyclic n-DABs, such as aromatic carbo-benzenes 4 (n = 3) where the alternating butatriene and butyne edges of the equivalent Kekule structures provide the three DAB units with a "hemi-butatriene" character. [9] In non-aromatic cyclic n-DABs, the two butatriene units of carbo-1,3-cyclohexadienes 5 are π-conjugated through the fusing triple bond (as in acyclic carbo-butadienes 2), [20] while the two π-independent DAB motifs of carbo-1,4-cyclohexadienes 6 (n = 2) [21] or carbo-barrelene 7 (n = 3) [22] are homoconjugated through two sp 3 -C atoms (Figure 1).…”
Section: Introductionmentioning
confidence: 99%